Cardioprotection Through Pharmacological Activation of Sirtuin 5 in a Murine Model of Acute Myocardial Infarction - Castiello C; Efentakis P; Nikolaou PE; Symeonidi L; Chania C; Barla I; Akrani I; Kostomitsopoulos N; Gikas E; Thomaidis NS; Mikros E; Kleinbongard P; et al. (Drug Design, Development and Therapy, 2025)
Carola Castiello,1,2 Panagiotis Efentakis,1 Panagiota-Efstathia Nikolaou,1 Lydia Symeonidi,1 Christina Chania,1 Ioanna Barla,3 Ifigeneia Akrani,4 Nikolaos Kostomitsopoulos,5 Evangelos Gikas,3 Nikolaos S Thomaidis,3 Emmanuel Mikros,4 Petra Kleinbongard,6 Rossella Fioravanti,2 Clemens Zwergel,2 Sergio Valente,2 Antonello Mai,2 Ioanna Andreadou1, † 1Laboratory of Pharmacology, Faculty of Pharmacy, National and Kapodistrian University of Athens, Athens, 15771, Greece; 2Department of Drug Chemistry and Technologies, Sapienza University of Rome, Rome, 00185, Italy; 3School of Chemistry, National and Kapodistrian University of Athens, Athens, 15772, Greece; 4Department of Pharmaceutical Chemistry, Faculty of Pharmacy, National and Kapodistrian University of Athens, Athens, 15771, Greece; 5Biomedical Research Foundation of the Academy of Athens, Athens, 11527, Greece; 6Institute for Pathophysiology, West German Heart and Vascular Center, University of Essen Medical School, Essen, 45122, Germany†Professor Ioanna Andreadou passed away on January 13, 2025Correspondence: Antonello Mai, Department of Drug Chemistry and Technologies, Sapienza University of Rome, Piazzale Aldo Moro 5, Rome, 00185, Italy, Tel +390649913392, Fax +3906491491, Email antonello.mai@uniroma1.it Panagiota-Efstathia Nikolaou, Laboratory of Pharmacology, Department of Pharmacy, Panepistimiopolis, Zografou, Athens, 15771, Greece, Tel +30-210-7274146, Fax +30 210 7274827, Email nayanik@pharm.uoa.grPurpose: Sirtuins (SIRTs) play a critical role in redox and metabolic regulation of the myocardium; however, the cardioprotective potential of SIRT5 in terms of infarct size (IS) reduction is still elusive. Herein, we employed the newly synthesized SIRT5-specific agonist, MC3215, developed by our group, to explore for the first time the pharmacological activation of SIRT5 as a target for cardioprotection.Methods and Results: In in vitro screening experiments, SIRT1 and SIRT5 agonists, namely, MC2606 and MC3215, at 1– 20 μ&Mgr; were added to cardiomyoblasts (H9c2) and human endothelial cells (EA.hy-926) during 24 h hypoxia/2 h reoxygenation (H/R). SIRT1 and SIRT5 agonists mitigated H/R injury. Male C57BL/6J mice underwent 30 min ischemia (I) followed by 2 h or 24 h reperfusion (R). Mice received vehicle, the SIRT1 or SIRT5 agonists at 20 and 30 mg/kg at the 20th min of ischemia, and IS was quantified via triphenyl-tetrazolium chloride staining (n=5– 7/group). MC3215-mediated SIRT5 activation reduced IS at 24 h R at 20mg/kg compared to controls (25.18± 2.7% vs 38.80± 4.7%). MC3215 treatment resulted in reduced protein malonylation in all experimental settings. Targeted mass-spectrometry-based metabolomics in the ischemic heart at the 10th min of R suggested increased fatty acid oxidation, as indicated by increased N3-Trimethyllysine and D-pantothenate. Concomitantly, molecular analysis indicated that the SIRT5 agonist activated AMPKα and Reperfusion Injury Salvage Kinase (RISK) pathway. Additionally, at 3 h reperfusion, MC3215 led to increased mitofusin 2 without altering apoptosis, paving towards improved mitochondrial dynamics. Co-administration of SIRT5 inhibitor, TW-37, abrogated MC3215-mediated cardioprotection.Conclusion: SIRT5 pharmacological agonism emerges as a novel cardioprotective target, leading to RISK pathway activation and mitochondria-related metabolic effects, converging at salvaging ischemic myocardium from I/R injury. Keywords: sirtuins, SIRT5, myocardial ischemia/reperfusion injury, cardioprotection